Problem Identification of Learning Chinese Proverbs at Faculty of Teacher Training and Education Tanjungpura University - Thamrin, Lily; Veronica, Tjen; Lusi, Lusi; Suhardi, Suhardi (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2022)
This research aims to reveal some problems in learning Mandarin Chinese Proverbs in the Mandarin Language Education Study Program FKIP Tanjungpura University. The research method used in this research is qualitative descriptive study. Researchers use documentation techniques and interview techniques in gathering the necessary data. The documentation technique is used to collect data from non-human sources, which consists of learning curricula, textbooks, reference books in the library of mandarin language education programs FKIP UNTAN. The interview technique is done indirectly through Google forms and then analyzed descriptively. The results of the study indicate that the problem of learning Mandarin proverbs are related to the curriculum, teaching materials and students. The curriculum applied by the FKIP mandarin language study program in Tanjungpura University is in accordance with what was proclaimed by the government, namely the Curriculum Based Indonesian National Qualification Framework (KKNI)-based Higher Education Curriculum but in the translation of the available courses there is still not enough attention to the learning of Mandarin proverbs, because learning Mandarin proverbs is only an insert in the middle of learning another new vocabulary. The availability of teaching materials is still an obstacle in learning Mandarin Chinese proverbs because textbooks are still very dependent on grants from the Chinese government, so the available teaching materials are still very limited. The textbooks used in learning Mandarin proverbs explanations are also incomplete. From the viewpoint of students, they realize the importance of learning Mandarin proverb towards improving Mandarin language skills. 72.2% of students thought that by mastering Mandarin proverbs, it can indicate person's Mandarin language skills were already very high and 96.7% of students claimed to have difficulty in learning Mandarin proverbs.